Analysis of factors influencing the distribution of 131-I in combined treatment of Licartin with transcatheter arterial chemoembolization in primary hepatic carcinoma - Tang, Ming; Li, Wen-Liang; Li, Jia-Yu; Lv, Juan; Chen, Fu-Kun; Zhu, Jia-Lun; Liu, Peng-Jie (Frontiers in Oncology, 2023)
Objective: To analyze the factors influencing the distribution of 131-I in the liver of patients with advanced hepatic carcinoma treated with the combination of Licartin (131I Metuximab) and transcatheter arterial chemoembolization (TACE). This study provides a reference and basis for the clinic on how to choose the best time for the treatment of Licartin and how to reduce other possible factors affecting the role of Licarti. Methods: Data from 41 patients with advanced hepatic carcinoma treated with the combination of Licartin and TACE in the Interventional Department of our hospital from March 2014 to December 2020 were collected. This included general characteristics, history of open and interventional surgery, interval between the last interventional surgery and the Licartin treatment, selected arteries in the Licartin perfusion, and 131-I distribution in the liver. Regression analysis was conducted to investigate the factors affecting the distribution of 131I in the liver. Results: In 14 cases (34.1%), 131-I was evenly distributed in the liver, and there was no correlation between the cause of even distribution with age（P = 0.939; OR:0.347-2.665）, previous open surgery history(P = 0.128;OR: 0.69518.097), previous history of interventional therapy(P = 0.072; OR: 0.0161.195), the interval between the last interventional surgery and the Licartin treatment(P = 0.883; OR: 0.1136.535), or the choice of the perfusion artery in the Licartin treatment (P = 0.419; OR: 0.5673.910). In 14 cases (34.1%), there was higher aggregation in the tumor than in the normal liver, which was related to previous interventional surgery (P = 0.043; OR: 1.06851.864). In 13 cases (31.7%), there was lower aggregation in the tumor than in the normal liver, which was related to the selected vessels in the Licartin perfusion (P = 0.013; OR: 0.0730.722). Conclusion: The effective aggregation of 131-I in the liver, even in tumors, the previous history of TACE, and the choice of vessels in the Licartin infusion might be the factors influencing the distribution of 131-I in the liver during hepatic artery infusion of Licartin in combination with TACE therapy.